Sentiment Analysis of Islamic Fintech: Uncovering the Pulse of Twitter Post-Covid-19 - Haidar, Abdullah; Hendrasto, Nur; Chairiyati, Fauziah; Herindar, Evania (PT Inovasi Pratama Internasional, 2024)
Twitter user attitude towards sharia fintech research provides an intriguing glimpse into perceptions and responses to sharia-based financial innovation. According to an analysis of 2,131 tweets, the bulk of attitudes were neutral (80.8%), followed by positive sentiments (16.2%), and the least were negative sentiments (3%). These findings paint an intriguing picture of how users react to sharia-compliant fintech concepts. The predominance of neutral attitude may indicate that the majority of Twitter users are not yet completely engaged with or have a neutral opinion of sharia fintech. This could be due to a lack of knowledge about the concept or a lack of direct connection with Islamic financial channels. The presence of strong positive sentiment, on the other hand, suggests interest in and support for this endeavour. There may be a view that sharia fintech can give a more ethical and in line with Islamic financial principles alternative. The unfavourable mood that has evolved, however, cannot be disregarded. Opinions opposing sharia fintech can stem from a variety of sources, including questions about its compatibility with authentic sharia principles or concerns about the hazards and security of its use. It is critical to understand the causes of unfavourable attitude and to improve education and transparency about sharia fintech. Overcoming questions and fears may necessitate an all-inclusive strategy to regulation, outreach, and risk management. In this approach, it can increase user trust and knowledge of the existence and benefits of sharia fintech in the current financial environment.